Analisis Penerimaan Pengguna Aplikasi Kipin School Menggunakan Metode Technology Acceptance Model (TAM) - Akbar, Yuma; Bachtiar, Yuliana (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
This study aims to analyze user acceptance of the Kipin School application in educational settings using the Technology Acceptance Model (TAM) approach. In the era of digital transformation, educational applications like Kipin School play a crucial role in enhancing the effectiveness, efficiency, and quality of learning. This application provides advanced features such as student management, lesson scheduling, academic reporting, and communication between teachers, students, and parents. The study evaluates perceived usefulness and perceived ease of use as the main dimensions influencing user attitude, behavioral intention to use, and actual system use of the application. The results of this research are expected to provide valuable insights for application developers to design more effective, innovative solutions that support the improvement of learning quality and educational management in the future. Additionally, this research is also expected to serve as a foundation for further studies in the field of technology acceptance in education.